1986
DOI: 10.1507/endocrj1954.33.743
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a single administration of somatostatin analogue (SMS 201-995) on GH, TSH and insulin secretion in patients with acromegaly.

Abstract: The effect of a long-acting somatostatin analogue SMS 201-995 on GH secretion was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The somatostatin analogue may have little influence in glucose tolerance because of its inhibitory effect on insulin secretion [21]. The balance of improving insulin sensitivity by lowering GH and decreasing insulin secretion in response to a somatostatin analogue has been suggested to influence glucose tolerance in patients with acromegaly [22]. However, another study has reported that the treatment with octreotide for 2-3 weeks did not alter the response to the 75 g oral glucose tolerance test in Japanese patients with acromegaly [23].…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…The somatostatin analogue may have little influence in glucose tolerance because of its inhibitory effect on insulin secretion [21]. The balance of improving insulin sensitivity by lowering GH and decreasing insulin secretion in response to a somatostatin analogue has been suggested to influence glucose tolerance in patients with acromegaly [22]. However, another study has reported that the treatment with octreotide for 2-3 weeks did not alter the response to the 75 g oral glucose tolerance test in Japanese patients with acromegaly [23].…”
Section: Acknowledgmentsmentioning
confidence: 99%